Pengaruh Konten Kreator Sadam Permana terhadap Efektivitas Diseminasi Informasi pada Masyarakat Digital - Leony Dwi Safitri; Desriyeni Desriyeni (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
The development of social media in the digital era has transformed the way people access and disseminate information. In addition to serving as a communication platform, social media has become a fast and far-reaching medium for information dissemination. However, the effectiveness of information dissemination continues to face several challenges, including low levels of digital literacy, limited public trust in information, and the overwhelming flow of online content. This study uses Sadam Permana as the research object because of his consistent efforts in presenting information on social issues through simple and easily understandable content. The purpose of this study is to examine the influence of content creator Sadam Permana on the effectiveness of information dissemination in digital society. This research employed a quantitative approach using a descriptive method. The study population consisted of approximately 467,000 followers of Sadam Permana's TikTok account as of the end of February 2026. The sample was selected using a purposive sampling technique, resulting in 100 respondents. Data were analyzed using the normality test, correlation test, linearity test, hypothesis test, and coefficient of determination test with the assistance of SPSS version 25. The findings indicate that Sadam Permana, as a content creator, has a significant influence on the effectiveness of information dissemination in digital society. The content creator variable obtained a mean score of 3.13, while the information dissemination effectiveness variable achieved a mean score of 2.92, both of which fall into the high category. Furthermore, the coefficient of determination (R Square) value of 0.553 indicates that the content creator variable explains 55.3% of the variance in information dissemination effectiveness, while the remaining 44.7% is influenced by other factors not examined in this study.